حاجة البنوك الإسلامية في الجزائر إلى معيار المحاسبة الإسلامي الأول - محمد, عبيد (Université de M'sila, 2020)
ملخص: تهدف الدراسة إلى إبراز حاجة البنوك الإسلامية الناشطة في الجزائر إلى معايير المحاسبة الإسلامية، وقد خصت الدراسة معيار المحاسبة الإسلامي الأول لما له من أهمية. واستخدم الباحث المنهج الوصفي في تبيان الجانب النظري من الدراسات السابقة، ليتم تلخيص أهم النقاط التي تميز محاسبة البنك الإسلامي وفق معيار المحاسبة الإسلامي الأول عن المحاسبة وفق النظام المحاسبي المالي البنكي، وتوصي الدراسة بضرورة إسراع الجزائر بإصدار نصوص تنظيمية تسهل تطبيق معايير المحاسبة الإسلامية في الجزائر. كلمات مفتاحية: البنوك الإسلامية، معايير المحاسبة الإسلامية، النظام المحاسبي المالي البنكي. تصنيف JEL : M41, M49 Abstract: the objective of study is reflected in the need of the Islamic banks which exercises these activities in Algeria in Islamic accounting norms, study concentrated on the first Islamic accounting norm seen its importance. The researcher used descriptive approach to show the theoretical aspect of the previous studies, to sum up the most important points which differentiate the accountancy of the Islamic Bank according to the first Islamic accounting norm of accountancy according to the banking financial accounting system. Study recommends in Algeria to publish fast regulation texts making easier the application of Islamic accounting norms in Algeria Keywords: Islamic bank; accounting norms Islamic; banking financial accounting system . Jel Classification Codes: : M41 ; M49. Résumé: l'objectif de l'étude se reflète dans le besoin des banques islamiques qui exerce ces activités en Algérie aux normes comptables islamiques, l'étude s'est concentrée sur la première norme comptable islamique vu son importance. Le chercheur a utilisé l'approche descriptive pour démontrer l'aspect théorique des études précédentes, afin de résumer les points les plus importants qui distinguent la comptabilité de la Banque islamique selon la première norme comptable islamique de la comptabilité selon le système de comptabilité financière . L'étude recommande à l'Algérie de publier rapidement des textes réglementaires facilitant l'application des normes comptables islamiques en Algérie. Mots-clés: Banque islamique; normes comptables islamique ;système comptable financier bancaire . Codes de classification de Jel: : M41 ; M49.
Keywords: البنوك الإسلامية ; معايير المحاسبة الإسلامية ; النظام المحاسبي المالي البنكي ; Islamic bank ; accounting norms Islamic ; banking financial accounting system